DEVELOPMENT OF THE ASSESSMENT OF ENVIRONMENTAL DAMAGE AND ENVIRONMENTAL RISKS IN CASE OF ACCIDENTS WITH OIL ON RAILWAY TRANSPORT - Zelenko, Yu. V. (Science and Transport Progress, 2010)
The principles of estimation of losses to the environment components caused by the emergency spills of petroleum products and the methodical approaches to estimation of ecological risk of functioning of railways are offered.